Is the development of obesogenic food environments a self-reinforcing process? Evidence from soft drink consumption - Fabrizio Ferretti; Michele Mariani; Elena Sarti (Globalization and Health, 2021)
Abstract Background Understanding how the development of obesogenic food environments and the consumption of ultra-processed foods and beverages influence each other can help policymakers to identify effective ways to curb the current obesity epidemic. This paper was designed to investigate whether, and to what extent, the consumption of soft drinks and the prevalence of obesity are linked through feedback effects. Methods An ecological study design and a simultaneous equation model were used to investigate the existence of a vicious cycle between the consumption of soft drinks and the prevalence of obesity. The analysis was based on a longitudinal dataset covering per capita sales of soft drinks, the age-standardised prevalence rate of obesity and several demographic and socio-economic control variables in a sample of 98 countries worldwide for the period 2005–2019. Results Using a Two-Stage Least Squares (2SLS) regression model with fixed effects, we documented a self-reinforcing process that links consumption and obesity. Changes in the spread of obesity were associated with changes in soft drink consumption: a one-unit increase in the age-adjusted prevalence rate of obesity increased consumption by about 2.39 l per person per year. Similarly, as the consumption of soft drinks rose, so did the prevalence of obesity: the age-adjusted rate of obesity increased by 0.07% for every additional litre consumed per capita. Computing the impact multipliers, we found that the outcome of a one-unit decrease in the average price of soft drinks was twofold: a) the prevalence of obesity increased by around 0.17%; and b) consumption increased by around 2.40 l per person, the sum of the increase directly caused by the price reduction (2 l) and the increase due to the interplay between consumption and obesity (0.4 l). Conclusions This study has identified a feedback loop between unhealthy habits (i.e. the consumption of soft drinks) and health outcomes (i.e. the prevalence of obesity). This interplay amplifies the impact of any exogenous changes in the determinants of consumption and obesity. These feedback effects should be considered and exploited in planning effective strategies to tackle the burden of obesity and the global epidemic of non-​communicable diseases.